Investigation of ifosfamide nephrotoxicity induced in a liver–kidney co‐culture biochip. Issue 2 (28th August 2012) - Choucha‐Snouber, Leila; Aninat, Caroline; Grsicom, Laurent; Madalinski, Geoffrey; Brochot, Céline; Poleni, Paul Emile; Razan, Florence; Guillouzo, Christiane Guguen; Legallais, Cécile; Corlu, Anne; Leclerc, Eric
Abstract: In this article, we present a liver–kidney co‐culture model in a micro fluidic biochip. The liver was modeled using HepG2/C3a and HepaRG cell lines and the kidney using MDCK cell lines. To demonstrate the synergic interaction between both organs, we investigated the effect of ifosfamide, an anticancerous drug. Ifosfamide is a prodrug which is metabolized by the liver to isophosforamide mustard, an active metabolite. This metabolism process also leads to the formation of chloroacetaldehyde, a nephrotoxic metabolite and acrolein a urotoxic one. In the biochips of MDCK cultures, we did not detect any nephrotoxic effects after 72 h of 50 µM ifosfamide exposure. However, in the liver–kidney biochips, the same 72 h exposure leads to a nephrotoxicity illustrated by a reduction of the number of MDCK cells (up to 30% in the HepaRG‐MDCK) when compared to untreated co‐cultures or treated MDCK monocultures. The reduction of the MDCK cell number was not related to a modification of the cell cycle repartition in ifosfamide treated cases when compared to controls. The ifosfamide biotransformation into 3‐dechloroethylifosfamide, an equimolar byproduct of the chloroacetaldehyde production, was detected by mass spectrometry at a rate of apparition of 0.3 ± 0.1 and 1.1 ± 0.3 pg/h/biochips in HepaRG monocultures and HepaRG‐MDCK co‐cultures respectively. Any metabolite was detected in HepG2/C3a cultures. Furthermore, the ifosfamide treatment in HepaRG‐MDCK co‐culture system triggered an increase in the intracellular calcium release in MDCK cells on contrary to the treatment on MDCK monocultures. As 3‐dechloroethylifosfamide is not toxic, we have tested the effect of equimolar choloroacetaldehyde concentration onto the MDCK cells. At this concentration, we found a quite similar calcium perturbation and MDCK nephrotoxicity via a reduction of 30% of final cell numbers such as in the ifosfamide HepaRG‐MDCK co‐culture experiments. Our results suggest that ifosfamide nephrotoxicity in a liver–kidney micro fluidic co‐culture model using HepaRG‐MDCK cells is induced by the metabolism of ifosfamide into chloroacetaldehyde whereas this pathway is not functional in HepG2/C3a‐MDCK model. This study demonstrates the interest in the development of systemic organ–organ interactions using micro fluidic biochips. It also illustrated their potential in future predictive toxicity model using in vitro models as alternative methods. Biotechnol. Bioeng. 2013; 110: 597–608. © 2012 Wiley Periodicals, Inc. Abstract : The authors develop a microfluidic biochip for liver renal tissues coculture. Liver HepaRG cells metabolize ifosfamide drugs whereas MDCK renal cells did not. Calcium release is enhanced in renal cells in the ifosfamide coculture demonstrating "systemic‐like interaction" between liver and kidney cells.